Can Functionalised Play Make Children Happy? A Critical Sociology Perspective - Frahsa, Annika; Thiel, Ansgar (Frontiers in Public Health, 2020)
The functionalisation of play basically stems from the diagnosis of a global childhood inactivity crisis, the so-called “children's obesity pandemic.” Hence, in the context of the activity-related guidelines, children's play appears no longer to be unproductive and purpose-free. It is rather considered an anti-obesity tool that will help children to meet physical activity recommendations. It is questionable whether such a functionalised tool can also provide what has been called the salience of the pleasures of free-play for children. Furthermore, a “normalization” of functionalised practices of play, in turn, could stigmatize children who do not or cannot adhere to these practices. Based upon this background, this paper will take a critical sociology perspective to analyse the functionalisation and medicalisation of children's play in an individualized, mediatized, and pedagogised society. In this sense, the paper aims to pay attention to how the primary goal of play in the sense of “simply make children happy” has given way to the goal of making them healthy and functional.